Sebuah Pendekatan Semantik: Kias dan Konotasi Pada Tiga Lirik Lagu Karya Banda Neira - Tasya Febrianty; Dea Putri Pascha Febryanti; Marshanda Amelya Octaviani; Yeni Rakhmawati Agustin; Endang Sholihatin (Universitas Sebelas Maret, 2025)
This article analyzes the semantics of three song lyrics in Banda Neira's “Yang patah tumbuh, yang hilang berganti” album, focusing on the use of figurative and connotative meanings. The purpose of this research is to; (1) find out the figurative and connotative meanings contained in the lyrics of the songs; and (2) find out the language style used in the three song lyrics. This research method uses descriptive qualitative method the author analyzes the data and then describes it narratively. The results of this study show that (1) through a combination of figurative and connotative meanings, Banda Neira presents lyrics that are not only aesthetically beautiful, but also rich in philosophical and emotional messages. Banda Neira's songs invite listeners to reflect on life's journey, accept limitations, and find peace in facing challenges. This combination produces works that evoke feelings and provide a wide room for interpretation for the listener. (2) the lyrics of the songs “Biru”, “Utarakan”, and “Langit dan Laut” have the same language style, namely, metaphor, simile, and personification.